Pengembangan Batik Surtanan Desa Serenan Kecamatan Juwiring Kabupaten Klaten - Aan Sudarwanto; Rahayu Adi Prabowo (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2022)
In the village of Serenan, in Surtanan, there is a group of batik that has the activity of nyerat (writing) cloth using batik wax. This activity is carried out according to orders from batik entrepreneurs from several regions in Solo and Yogyakarta. The order is in the form of a pattern (writing/image) that has been determined by the batik entrepreneur. Based on initial observations, it is known that there are several problems that become obstacles for these craftsmen. These obstacles, among others, the Surtanan batik group, chaired by Sri Suyamti, was originally a regional community development program under the guidance of batik entrepreneurs and the district government. However, as the development of batik production in each batik producer is different, this group tends to wait and does not have the motivation to develop their creativity. In addition, there are other problems, namely the lack of production and marketing strategies. Based on these problems, the author wants to carry out training and mentoring activities, targeting the Surtanan batik group. The focus of this activity is more directed at aspects of improving production techniques and production quality. By doing several approaches such as assistance in making batik based on product development through technical colet. Then the strengthening of human resources is carried out through the introduction of design development, which is expected to increase the variety of batik production so that it can increase market and business competitiveness.